Fault array evolution above a reactivated rift fabric; a subsurface example from the northern Horda Platform fault array - Whipp,PS; Jackson,CAL; Gawthorpe,RL; Dreyer,T; Quinn,D (Basin Research, 2014)
The impact of a pre-existing rift fabric on fault array evolution during a subsequent phase of lithospheric extension is investigated using 2D and 3D seismic reflection, and borehole data from the northern Horda Platform, Norwegian North Sea. Two fault populations are developed: (i) a population comprising relatively tall (>2 km), N-S-striking faults, which have >1.5 km of throw. These faults are up to >60 km long, penetrate down into crystalline basement and bound the eastern margins of 6-15 km wide half-graben, which contain >3 km of pre-Jurassic, likely Permo-Triassic, but possibly Devonian age syn-rift strata; and (ii) a population comprising vertically restricted (<1 km), NW-SE-striking faults, which are more closely-spaced (0.5-5 km), have lower displacements (30-100 m) and not as long (2-10 km) as those in the N-S-striking population. The NW-SE-striking population typically occur between the N-S-striking population, and may terminate against or cross-cut the larger structures. NW-SE-striking faults do not bound pre-Jurassic half-graben and are largely restricted to the Jurassic-to-Cretaceous succession. Seismic-stratigraphic observations and the stratigraphic position of the fault tips in both fault populations allow us to reconstruct the Late Jurassic-to-Early Cretaceous growth history of the northern Horda Platform fault array. We suggest the large, N-S-striking population was active during the Permo-Triassic and possibly earlier (Devonian?), before becoming inactive and buried during the Early and Middle Jurassic. After a period of relative tectonic quiescence and in response to Late Jurassic extension, the N-S-striking, pre-Jurassic fault population propagated through the Early-Middle Jurassic cover and individual fault systems rapidly (within <10 Ma) established their maximum length. These fault systems became the dominant structures in the newly formed fault array and defined the locations of the main, Late Jurassic-to-Early Cretaceous